Sulfide solid electrolyte and preparation method and application thereof

By combining dry ball milling for amorphization with wet ball milling and solid-state sintering, the problems of pure phase and performance in the preparation of sulfide solid electrolytes were solved, enabling the efficient preparation of submicron or nanoscale pure phase sulfide electrolytes and improving battery performance.

CN120922895APending Publication Date: 2025-11-11ZIJIN MINING RENEWABLE ENERGY & ADVANCED MATERIALS (CHANGSHA) CO LTD

Patent Information

Application Number
CN202510827047.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-19
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing technologies struggle to achieve high-purity phases and high-performance submicron or nanometer-sized particles when preparing sulfide solid electrolytes, and traditional methods suffer from low efficiency and impurity phase formation.

Method used

After dry ball milling of amorphous raw materials, a precursor slurry with a particle size of 0.05-0.5μm was prepared by wet ball milling. Subsequently, solid-state sintering was carried out in an inert atmosphere to avoid secondary grinding and obtain a pure phase sulfide solid electrolyte.

Benefits of technology

It enables the preparation of high-performance submicron or nanoscale pure-phase sulfide electrolytes without secondary grinding, improving electrode/electrolyte interface contact, reducing impedance, and enhancing the performance of all-solid-state sulfide batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120922895A_ABST
    Figure CN120922895A_ABST
Patent Text Reader

Abstract

The invention provides a sulfide solid electrolyte and a preparation method and application thereof, and relates to the technical field of lithium ion batteries. The preparation method comprises the following steps: S1, carrying out dry ball milling treatment on raw materials Li2S, P2S5 and LiX according to a required stoichiometric ratio, so that the raw materials are amorphized; s2, adding a solvent into the non-crystallized raw material obtained in the step S1, and carrying out wet ball-milling treatment to obtain a precursor with the particle size of 0.05-0.5 mu m; s3, the solvent is removed from the precursor slurry, the sulfide solid electrolyte is obtained through solid-phase sintering, all the steps are carried out in an inert atmosphere, and X is a halogen element. According to the present invention, the non-crystallization of the raw material is achieved through the dry ball milling, the uniform precursor slurry with the small particle size is obtained by combining the wet ball milling, and the sub-micron / nano-scale pure phase electrolyte material can be obtained after the sintering treatment, such that the electrode / electrolyte interface contact is improved, the impedance is reduced, and the battery performance is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a sulfide solid electrolyte, its preparation method, and its application. Background Technology

[0002] All-solid-state lithium batteries are considered the most promising next-generation electrochemical energy storage technology due to their high energy density, excellent safety performance, and long cycle life. Among these, the solid electrolyte, as the core component of all-solid-state batteries, directly affects battery performance and industrialization. Sulfide solid electrolytes, with their high ionic conductivity and good mechanical properties, have become a current research hotspot. However, the large-scale preparation of sulfide solid electrolytes still faces many challenges. Traditional preparation methods mainly include dry ball milling followed by sintering and wet ball milling followed by sintering, but both have significant drawbacks: during dry ball milling, the raw materials tend to adhere to the inner wall of the milling jar, leading to uneven reaction, requiring frequent jar emptying, resulting in low efficiency, and making it difficult to achieve uniform preparation of nanoscale particles. During wet ball milling, some sulfides may partially dissolve or complex in organic solvents, leading to the formation of impurity phases after sintering, reducing the ionic conductivity of the electrolyte.

[0003] Therefore, there is an urgent need to provide a method for preparing high-performance submicron or nanoscale pure-phase sulfide electrolytes. Existing technology CN119230924A discloses a submicron-scale sulfide solid electrolyte and its preparation method, which includes the following steps: weighing appropriate amounts of Li₂S, P₂S₅, and LiX as raw materials, where X is a halogen element; mechanically grinding the raw materials to obtain a sulfide solid electrolyte precursor; sintering the sulfide solid electrolyte precursor and cooling it at room temperature to obtain a large-particle-size sulfide solid electrolyte; and mechanically grinding the large-particle-size sulfide solid electrolyte to obtain a submicron-scale sulfide solid electrolyte. Obviously, although this preparation method can produce a submicron-scale sulfide solid electrolyte, it involves a secondary grinding of the sintered large-particle-size sulfide solid electrolyte. This secondary grinding leads to a significant decrease in the lithium-ion conductivity of the electrolyte, resulting in poor performance when matched with all-solid-state batteries.

[0004] Therefore, the current production of sulfide electrolytes urgently needs a method to prepare submicron or nanoscale pure-phase sulfide electrolytes without secondary grinding after sintering. Summary of the Invention

[0005] This invention provides a sulfide solid electrolyte, its preparation method, and its application, which solves the problem that the preparation of submicron or nanoscale sulfide electrolytes in the prior art is difficult to achieve both high purity phase and high performance. This invention realizes the preparation of high-performance submicron or nanoscale pure phase sulfide electrolytes.

[0006] In a first aspect, the present invention provides a method for preparing a sulfide solid electrolyte, comprising the following steps: S1. Dry ball mill the raw materials Li2S, P2S5 and LiX according to the required stoichiometric ratio to make the raw materials amorphous; S2. Add solvent to the amorphous raw material obtained in S1, and perform wet ball milling to obtain a precursor with a particle size of 0.05-0.5 μm; S3. Remove the solvent from the precursor slurry obtained in S2 and perform solid-state sintering to obtain the sulfide solid electrolyte Li. 7-a PS 6- a X a Where 1≤a≤2, All the above steps are carried out in an inert atmosphere, where X is a halogen element.

[0007] According to the present invention, a sulfide solid electrolyte preferably has a ball-to-material ratio of (10~50):1 in the dry ball milling process in S1, and / or a rotation speed of 300~900 rpm, and / or a time of 5~20 h.

[0008] According to the sulfide solid electrolyte provided by the present invention, more preferably, the ball-to-material ratio of dry ball milling in S1 is (20~40):1, and / or the rotation speed is 500~600 rpm, and / or the time is 10~15 h.

[0009] According to the present invention, in a sulfide solid electrolyte, preferably, the solvent in S2 is a nonpolar and / or weakly polar organic solvent.

[0010] According to the present invention, in a sulfide solid electrolyte, preferably, the mass ratio of solvent to amorphous raw material in S2 is (0.1~2):1.

[0011] According to the present invention, a sulfide solid electrolyte preferably has a ball-to-material ratio of (10~50):1 in the wet ball milling process of S2, and / or a rotation speed of 300~900 rpm, and / or a time of 1~10 h.

[0012] According to the present invention, a sulfide solid electrolyte preferably has the following characteristics: in S2, the ball-to-material ratio of wet ball milling is (20~40):1, and / or the rotation speed is 500~600 rpm, and / or the time is 2~5 h. According to the present invention, the solvent removal in S3 is preferably carried out by vacuum drying at a temperature of 50-150°C for a time of 10-40 h; and / or the sintering temperature in S3 is 400-600°C for a time of 5-25 h.

[0013] Secondly, the present invention also provides a sulfide solid electrolyte prepared by the method of preparing sulfide solid electrolyte according to the present invention, wherein the sulfide solid electrolyte is a pure phase and the particle size D50 is 0.5~0.9μm.

[0014] Thirdly, the present invention also provides the application of a sulfide solid electrolyte in the preparation of an all-solid-state battery.

[0015] Fourthly, the present invention also provides an all-solid-state battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is a sulfide solid electrolyte provided by the present invention.

[0016] Beneficial effects: This invention provides a method for preparing sulfide solid electrolytes. The method achieves amorphization of raw materials through dry ball milling, solving the problems of raw material volatilization and dissolution after the addition of solvents. Furthermore, wet ball milling is used to obtain a precursor slurry with small and uniform particle size. After sintering, submicron / nano-scale pure phase electrolyte materials can be obtained. There is no need to perform secondary grinding on the sintered sulfide solid electrolyte particles. Submicron or nano-scale pure phase electrolytes can be directly prepared. Nanoparticles can improve the electrode / electrolyte interface contact, reduce impedance, and significantly improve the performance of all-solid-state sulfide solid batteries. Attached Figure Description

[0017] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings.

[0018] Figure 1 The images show the XRD patterns of the sulfide solid electrolytes prepared in Example 1 and Comparative Examples 1-3.

[0019] Figure 2 EIS impedance diagrams of the sulfide solid electrolytes prepared in Example 1 and Comparative Examples 1-3.

[0020] Figure 3 SEM images of the sulfide solid electrolytes prepared in Example 1 and Comparative Example 2. Detailed Implementation

[0021] The following examples are for illustrative purposes only and are not intended to limit the scope of the invention. Where specific techniques or conditions are not specified in the examples, they should be performed according to the techniques or conditions described in the literature in this field, or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased from legitimate channels.

[0022] This invention provides a method for preparing a sulfide solid electrolyte, comprising the following steps: S1. Dry ball milling raw materials Li2S, P2S5 and LiX according to the required stoichiometric ratio to amorphize the raw materials; S2. Add solvent to the amorphous raw material obtained in S1, and perform wet ball milling to obtain a precursor with a particle size of 0.05-0.5 μm; S3. Remove the solvent from the precursor slurry obtained in S2 and perform solid-state sintering to obtain the sulfide solid electrolyte Li. 7-a PS 6- a X a Where 1≤a≤2, All the above steps are carried out in an inert atmosphere, where X is a halogen element.

[0023] In some specific embodiments, the X halogen element of the present invention can be at least one of Cl, Br or I.

[0024] It should be noted that: In the preparation method of the sulfide solid electrolyte of the present invention, step S1 first treats the raw material by dry ball milling to obtain an amorphous raw material. The amorphous raw material solves the problems of raw material volatilization and dissolution after solvent addition, avoiding the reaction of sulfides in the raw material (including dissolution or complexation) during subsequent wet ball milling. Combined with the wet ball milling treatment in step S2 of the present invention, a small-particle-size precursor slurry can be obtained. The above-treated precursor slurry is then sintered to obtain the target submicron or nanoscale pure-phase sulfide electrolyte. Furthermore, the wet ball milling process avoids the reaction of sulfides in organic solvents, further ensuring no impurity phase formation after sintering and preventing a decrease in electrolyte ionic conductivity, resulting in a high-purity phase and high performance.

[0025] In a specific implementation, in order to fully realize the amorphization of the raw materials, the parameters such as the ball-to-material ratio, rotation speed, and ball milling time of the dry ball milling are further optimized. Preferably, the ball-to-material ratio of the dry ball milling in S1 is (10~50):1, and / or the rotation speed is 300~900 rpm, and / or the time is 5~20h.

[0026] In some specific embodiments, more preferably, the ball-to-material ratio of dry ball milling in S1 is (20~40):1, and / or the rotation speed is 500~600 rpm, and / or the time is 10~15 h.

[0027] Sulfide solid electrolytes are extremely sensitive to polar solvents and are prone to decomposition or side reactions. In some specific embodiments, the solvent used in the wet ball milling of S2 of the present invention can be a non-polar and / or weakly polar organic solvent, which does not react with sulfides and can maintain the stability of the material.

[0028] In some specific embodiments, the non-polar or weakly polar organic solvent mentioned in this invention may be at least one of xylene, toluene, n-heptane, hexane, octane or anisole, preferably n-heptane or xylene.

[0029] One purpose of adding solvent after dry ball milling and then performing wet ball milling is to allow the material that sticks to the tank wall due to dry ball milling to detach from the tank wall in the presence of solvent. Furthermore, to control solids content, optimize the wet grinding effect, and obtain a precursor slurry with a smaller particle size, in some specific embodiments, the mass ratio of solvent to amorphous raw material in S2 is preferably (0.1~2):1, more preferably (0.4~1.5):1. For example, it can be values ​​such as 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, or a range of values ​​composed of any of these points.

[0030] After dry ball milling, the material sticks to the wall. Wet ball milling can remove the sticking material. In order to carry out more thorough wet ball milling and to reduce the particle size of the precursor after dry ball milling, it is more conducive to the preparation of submicron / nano-scale sulfide solid electrolytes after sintering. In some specific embodiments, the ball-to-material ratio of wet ball milling in S2 is (10~50):1, and / or the rotation speed is 300~900 rpm, and / or the time is 1~10h.

[0031] In some other specific embodiments, it is more preferable that the ball-to-material ratio of wet ball milling in S2 is (20~40):1, and / or the rotation speed is 500~600 rpm, and / or the time is 2~5 h.

[0032] In some specific embodiments, the conditions for wet grinding can be, for example: The ball-to-material ratio for wet ball milling is 10:1, 20:1, 30:1, 40:1, or 50:1, and / or the rotational speed is 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, or 900 rpm, and / or the time is 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h. Alternatively, it can be a range of values ​​composed of any points within the range.

[0033] In some specific embodiments, S3 solvent removal is performed by vacuum drying at a temperature of 50~150℃ for 10~40h.

[0034] In some other specific embodiments, it is more preferable that the vacuum drying temperature in S3 is 80~100°C and the drying time is 12~20h.

[0035] In some specific embodiments, the vacuum drying conditions in S3 can be, for example, point values ​​such as drying temperature of 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, and 150℃, and point values ​​such as drying time of 10h, 12h, 20h, 30h, and 40h. Alternatively, they can be a range of any of these point values.

[0036] In some specific embodiments, it is also preferred that the sintering temperature in S3 is 400~600℃ and the sintering time is 5~25h.

[0037] In some other specific embodiments, it is more preferable that the sintering temperature in S3 is 450~550℃ and the drying time is 10~20h.

[0038] In some specific embodiments, the sintering conditions in S4 can be, for example, point values ​​such as sintering temperature of 400℃, 450℃, 500℃, 550℃, 600℃, etc., and point values ​​such as sintering time of 5h, 10h, 15h, 20h, 25h, etc., or a range of values ​​composed of any of these point values.

[0039] The present invention also specifically provides a sulfide solid electrolyte prepared according to the preparation method of sulfide solid electrolyte. In some embodiments, the sulfide solid electrolyte is a pure phase with a particle size D50 of 0.5~0.9μm.

[0040] In a specific embodiment of the present invention, the particle size D50 of the sulfide solid electrolyte is a point value of 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, etc., or it can be a range of any point value.

[0041] This invention also provides the application of a sulfide solid electrolyte in the preparation of all-solid-state batteries.

[0042] The present invention also provides an all-solid-state battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is a sulfide solid electrolyte provided by the present invention.

[0043] Example 1 A Li6PS5Cl sulfide solid electrolyte is prepared by the following steps: S1: Weigh 10g of electrolyte raw materials Li2S:P2S5:LiCl according to the stoichiometric ratio (molar ratio) 5:1:2. Place the raw materials into a ball mill jar for dry ball milling to make the raw materials amorphous. The ball-to-material ratio is 40:1, the rotation speed is 500rpm / min, and the ball milling time is 10h. S2: Add 10g of xylene solvent to the ball mill jar of step S1 and perform wet ball milling to obtain precursor slurry. The ball-to-material ratio remains unchanged, the rotation speed is 500rpm / min, the ball milling time is 2h, and the precursor particle size is 0.1~0.3μm. S3: The precursor slurry obtained in step S2 is dried at 80°C for 12 hours under a vacuum of -0.1 MPa. The vacuum-dried electrolyte precursor is then sintered at 550°C for 15 hours under an argon atmosphere to obtain Li6PS5Cl sulfide solid electrolyte.

[0044] The phase composition, particle size, and ionic conductivity of the sulfide solid electrolyte prepared in Example 1 were tested.

[0045] The test results are shown in Table 1.

[0046] Example 2 A Li6PS5Br sulfide solid electrolyte is prepared by the following steps: S1: Weigh 10g of electrolyte raw materials Li2S:P2S5:LiBr according to the stoichiometric ratio (molar ratio) 5:1:2. Place the raw materials into a ball mill jar for dry ball milling to make the raw materials amorphous. The ball-to-material ratio is 40:1, the rotation speed is 600rpm / min, and the ball milling time is 10h. S2: Add 10g of xylene solvent to the ball mill jar of step S1 for wet ball milling. The ball-to-material ratio remains unchanged, the rotation speed is 500rpm / min, the ball milling time is 2h, and the precursor particle size is 0.1~0.3μm. S3: The precursor slurry obtained in step S2 is dried at 80°C for 12 hours under a vacuum of -0.1 MPa. The vacuum-dried electrolyte precursor is then sintered at 520°C for 15 hours under an argon atmosphere to obtain Li6PS5Br sulfide solid electrolyte.

[0047] The detection methods for its phase, particle size and ionic conductivity are as described in Example 1, and the detection results are shown in Table 1.

[0048] Example 3 A Li6PS5I sulfide solid electrolyte is prepared by the following steps: S1: Weigh 10g of electrolyte raw material Li2S:P2S5:LiI according to the stoichiometric ratio of 5:1:2 (molar ratio), put the raw material into a ball mill jar for dry ball milling to make the raw material amorphous. The ball-to-material ratio is 40:1, the rotation speed is 600rpm / min, and the ball milling time is 10h. S2: Add 10g of xylene to the ball mill jar of step S1 for wet ball milling. The ball-to-material ratio remains unchanged, the rotation speed is 500rpm / min, the ball milling time is 2h, and the precursor particle size is 0.05~0.2μm. S3: The precursor slurry obtained in step S2 is dried at 80°C for 12 hours under a vacuum of -0.1 MPa. The vacuum-dried electrolyte precursor is then sintered at 480°C for 15 hours under an argon atmosphere to obtain Li6PS5I sulfide solid electrolyte.

[0049] The detection methods for its phase, particle size and ionic conductivity are as described in Example 1, and the detection results are shown in Table 1.

[0050] Example 4 A Li 5.5 PS 4.5 Cl 1.5 A sulfide solid electrolyte, the preparation method of which includes the following steps: S1: Weigh 10g of electrolyte raw materials Li2S:P2S5:LiCl according to the stoichiometric ratio (molar ratio) 4:1:3. Place the raw materials into a ball mill jar for dry ball milling with a ball-to-material ratio of 40:1, a rotation speed of 600rpm / min, and a milling time of 10h. S2: Add 10g of xylene to the ball mill jar of step S1 for wet ball milling. The ball-to-material ratio remains unchanged, the rotation speed is 500rpm / min, the ball milling time is 2h, and the precursor particle size is 0.15~0.35μm. S3: The precursor slurry obtained in step S2 was dried at 80°C for 12 hours under a vacuum of -0.1 MPa. The vacuum-dried electrolyte precursor was then sintered at 500°C for 15 hours under an argon atmosphere to obtain Li. 5.5 PS 4.5 Cl 1.5 Sulfide solid electrolyte.

[0051] The detection methods for its phase, particle size and ionic conductivity are as described in Example 1, and the detection results are shown in Table 1.

[0052] Example 5 A Li 5.5 PS 4.5 Cl 0.75 Br 0.75 A sulfide solid electrolyte, the preparation method of which includes the following steps: S1: Weigh 10g of electrolyte raw materials Li2S:P2S5:LiCl:LiBr according to the stoichiometric ratio (molar ratio) 4:1:1.5:1.5. Place the raw materials into a ball mill jar for dry ball milling with a ball-to-material ratio of 40:1, a rotation speed of 600rpm / min, and a milling time of 10h. S2: Add 10g of xylene to the ball mill jar of step S1 for wet ball milling. The ball-to-material ratio remains unchanged, the rotation speed is 500rpm / min, the ball milling time is 2h, and the precursor particle size is 0.08~0.2μm. S3: The precursor slurry obtained in step S2 was dried at 80°C for 12 hours under a vacuum of -0.1 MPa. The vacuum-dried electrolyte precursor was then sintered at 480°C for 15 hours under an argon atmosphere to obtain Li. 5.5 PS 4.5 Cl 0.75 Br 0.75 Sulfide solid electrolyte.

[0053] The detection methods for its phase, particle size and ionic conductivity are as described in Example 1, and the detection results are shown in Table 1.

[0054] Example 6 A Li6PS5Cl sulfide solid electrolyte is prepared in a manner that is basically the same as that in Example 1, except that the ball-to-material ratio in the dry ball milling in S1 is 10:1, the rotation speed is 600 rpm / min, and the time is 10 h.

[0055] Example 7 A Li6PS5Cl sulfide solid electrolyte is prepared in a manner that is basically the same as that in Example 1, except that the ball-to-material ratio of the dry ball milling in S1 is 40:1, the rotation speed is 600 rpm / min, and / or the time is 5 h.

[0056] Example 8 A Li6PS5Cl sulfide solid electrolyte is prepared in a manner that is basically the same as in Example 1, except that the ball-to-material ratio of the wet ball milling in S2 is 10:1, the rotation speed is 600 rpm / min, and the time is 2 h.

[0057] Example 9 A Li6PS5Cl sulfide solid electrolyte is prepared in a manner that is basically the same as in Example 1, except that the ball-to-material ratio of the wet ball milling in S2 is 40:1, the rotation speed is 600 rpm / min, and the time is 1 h.

[0058] Comparative Example 1 This comparative example provides a method for preparing Li6PS5Cl sulfide solid electrolyte by dry ball milling: Weigh 10g of electrolyte raw materials Li2S:P2S5:LiCl according to a stoichiometric ratio of 5:1:2. Place the raw materials into a ball mill jar for dry ball milling at a ball-to-material ratio of 40:1, a rotation speed of 500rpm / min, and a milling time of 10h.

[0059] The electrolyte precursor was sintered at 550°C for 15 h under an argon atmosphere by dry ball milling to obtain Li6PS5Cl sulfide solid electrolyte.

[0060] The detection methods for its phase, particle size and ionic conductivity are as described in Example 1, and the detection results are shown in Table 1.

[0061] Comparative Example 2 This comparative example provides a method for preparing Li6PS5Cl sulfide solid electrolyte by dry ball milling: Weigh 10g of electrolyte raw materials Li2S:P2S5:LiCl according to a stoichiometric ratio of 5:1:2. Place the raw materials into a ball mill jar for dry ball milling at a ball-to-material ratio of 40:1 and a rotation speed of 500 rpm / min. The total ball milling time is 10 hours. After 5 hours of ball milling, the jar needs to be emptied and then ball milling continues for another 5 hours.

[0062] The electrolyte precursor was sintered at 550°C for 15 h under an argon atmosphere by dry ball milling to obtain Li6PS5Cl sulfide solid electrolyte.

[0063] The detection methods for its phase, particle size and ionic conductivity are as described in Example 1, and the detection results are shown in Table 1.

[0064] Comparative Example 3 This comparative example provides a method for preparing Li6PS5Cl sulfide solid electrolyte by wet ball milling: Weigh 10g of electrolyte raw materials Li2S:P2S5:LiCl according to a stoichiometric ratio of 5:1:2. Place the raw materials into a ball mill jar, add 10g of xylene, and perform wet ball milling with a ball-to-material ratio of 40:1, a rotation speed of 500rpm / min, and a milling time of 10h.

[0065] The precursor slurry obtained by wet ball milling was dried at 80°C for 12 hours under a vacuum of -0.1 MPa.

[0066] The vacuum-dried electrolyte precursor was sintered at 550°C for 15 h in an argon atmosphere to obtain Li6PS5Cl sulfide solid electrolyte.

[0067] The detection methods for its phase, particle size and ionic conductivity are as described in Example 1, and the detection results are shown in Table 1.

[0068] The performance of the sulfide solid electrolytes in the above embodiments and comparative examples was tested. The specific testing methods are as follows: The purity of the sulfide solid electrolyte was characterized by XRD phase analysis. The XRD patterns of the sulfide solid electrolytes prepared in Example 1 and Comparative Examples 1-3 are shown below. Figure 1 As shown.

[0069] The particle size of the sulfide solid electrolyte was tested using a laser particle size analyzer at a dew point of -50°C.

[0070] The ionic conductivity of the sulfide solid electrolyte was tested. The test conditions were as follows: 100 mg of electrolyte powder was pressed into a 10 mm diameter battery mold using a powder press, and the bulk impedance Re of the sample was measured using an electrochemical workstation at 25°C. The EIS impedance diagrams of the sulfide solid electrolytes prepared in Example 1 and Comparative Examples 1-3 are shown below. Figure 2 As shown, the ionic conductivity of the sample is calculated using the formula σ=d / (Re*S).

[0071] Figure 3 The images show SEM images of the sulfide solid electrolytes prepared in Example 1 and Comparative Example 2. It can be seen from the images that the particle size of Comparative Example 2 after dry ball milling and inverted tank treatment is still much larger than that of Example 1, which was first dry ball milled and then wet ball milled.

[0072] Table 1

[0073] Examples 1-9, employing a dry ball milling amorphization combined with wet ball milling, all yielded pure-phase products with submicron particle sizes. In contrast, Comparative Example 1, using pure dry ball milling, may have resulted in uneven mixing of raw materials and the formation of impurities due to the lack of inverted mixing. Comparative Example 2, using pure dry ball milling with inverted mixing, yielded pure-phase products, but this process was time-consuming and labor-intensive, and the product particle size was relatively large. Comparative Example 3, using pure wet ball milling, produced small particle sizes, but the potential for raw material dissolution leading to impurities, and its conductivity was only 0.98 mS / cm. This invention demonstrates the advantages of the dry ball milling amorphization combined with wet ball milling process in terms of purity and particle size control.

[0074] Among them, the ionic conductivity of sulfide solid electrolytes is positively correlated with the electrolyte particle size; for the same electrolyte, the larger the particle size, the higher the ionic conductivity. Compared with Example 1, the dry ball milling in Examples 6 and 7 was not as thorough, but the wet ball milling was thorough, so their particle size was close to that of Example 1. However, the ionic conductivity was lower due to the less thorough dry ball milling. In Examples 8 and 9, the wet ball milling was less thorough after dry ball milling, resulting in a larger precursor particle size. Therefore, the electrolyte particle size was larger after sintering, and its conductivity was higher.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a sulfide solid electrolyte, characterized in that, Includes the following steps: S1. Dry ball mill the raw materials Li2S, P2S5 and LiX according to the required stoichiometric ratio to make the raw materials amorphous; S2. Add solvent to the amorphous raw material obtained in S1, and perform wet ball milling to obtain a precursor with a particle size of 0.05~0.5μm; S3. Remove the solvent from the precursor slurry obtained in S2 and perform solid-state sintering to obtain the sulfide solid electrolyte Li. 7-a PS 6-a X a Where 1≤a≤2, All the above steps are carried out in an inert atmosphere, where X is a halogen element.

2. The method for preparing the sulfide solid electrolyte according to claim 1, characterized in that, In S1, the ball-to-material ratio of dry ball milling is (10~50):1, and / or the rotation speed is 300~900 rpm, and / or the time is 5~20 h.

3. The method for preparing the sulfide solid electrolyte according to claim 2, characterized in that, In S1, the ball-to-material ratio of dry ball milling is (20~40):1, and / or the rotation speed is 500~600 rpm, and / or the time is 10~15 h.

4. The method for preparing the sulfide solid electrolyte according to claim 1, characterized in that, The solvent in S2 is a nonpolar and / or weakly polar organic solvent, and / or the mass ratio of the solvent in S2 to the amorphous raw material is (0.1~2):

1.

5. The method for preparing the sulfide solid electrolyte according to claim 1, characterized in that, In S2, the ball-to-material ratio for wet ball milling is (10~50):1, and / or the rotation speed is 300~900 rpm, and / or the time is 1~10 h.

6. The method for preparing the sulfide solid electrolyte according to claim 5, characterized in that, In S2, the ball-to-material ratio for wet ball milling is (20~40):1, and / or the rotation speed is 500~600 rpm, and / or the time is 2~5 h.

7. The method for preparing the sulfide solid electrolyte according to claim 1, characterized in that, Solvent removal in S3 is achieved by vacuum drying at a temperature of 50-150℃ for 10-40 hours; and / or sintering in S3 is achieved at a temperature of 400-600℃ for 5-25 hours.

8. A sulfide solid electrolyte prepared by the method of any one of claims 1 to 7, characterized in that, The sulfide solid electrolyte is a pure phase with a particle size D50 of 0.5~0.9μm.

9. The application of the sulfide solid electrolyte of claim 8 in the preparation of an all-solid-state battery.

10. An all-solid-state battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The electrolyte is the sulfide solid electrolyte as described in claim 8.

Citation Information

Patent Citations

  • Submicron sulfide solid electrolyte and preparation method thereof

    CN119230924A

Cited By

  • Lithium sulfide and its preparation method and application, solid-state electrolyte

    CN121516824A

  • Small-particle-size sulfide solid electrolyte material and preparation method and application thereof

    CN122158683A